2017
DOI: 10.1007/s40279-017-0689-z
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Exertional Rhabdomyolysis

Abstract: Exertional (exercise-induced) rhabdomyolysis is a potentially life threatening condition that has been the subject of research, intense discussion, and media attention. The causes of rhabdomyolysis are numerous and can include direct muscle injury, unaccustomed exercise, ischemia, extreme temperatures, electrolyte abnormalities, endocrinologic conditions, genetic disorders, autoimmune disorders, infections, drugs, toxins, and venoms. The objective of this article is to review the literature on exertional rhabd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 145 publications
(183 reference statements)
1
77
2
5
Order By: Relevance
“…11,15 However, it is known that some factors increase the risk of rhabdomyolysis such as underlying diseases such as McArdle disease and myopathies, dehydration, supplement or drug use (eg, statins), environmental heat stress, or sickle cell trait. 17 In the present study, no participants seemed to have these risk factors. It should be noted that similar exercises to those of the present study could be performed by people in a gym.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…11,15 However, it is known that some factors increase the risk of rhabdomyolysis such as underlying diseases such as McArdle disease and myopathies, dehydration, supplement or drug use (eg, statins), environmental heat stress, or sickle cell trait. 17 In the present study, no participants seemed to have these risk factors. It should be noted that similar exercises to those of the present study could be performed by people in a gym.…”
Section: Discussioncontrasting
confidence: 46%
“…When severe muscle damage is induced by eccentric exercises, there is a potential risk of exertional rhabdomyolysis. [15][16][17] It is possible that performing bilateral eccentric exercises targeting several different muscles in one session increases a risk of exertional rhabdomyolysis. However, no previous study has reported the magnitude of increases in CK activity and Mb concentration in the blood after performing several eccentric resistance exercises in one session.…”
Section: Introductionmentioning
confidence: 99%
“…Rhabdomyolysis is a condition not exclusive of CrossFit, since other sports, if performed strenuously, can also cause it. It usually occurs due to poor exercise prescription or execution without adequate supervision 46 , factor of which is also associated with injuries in CrossFit, as verified in the study by Weisenthal et al 22 , where the injury rate was significantly decreased with the involvement of the instructor.…”
Section: Body Regions Affected and Type Of Exercisementioning
confidence: 87%
“…Det synes å vaere en viss genetisk disposisjon for å utvikle rabdomyolyse (24,25), men den viktigste faktoren er hvordan man trener. Derfor skal man vaere spesielt forsiktig når man igangsetter trening som innebaerer stort eksentrisk muskelarbeid.…”
Section: +unclassified